Anmeldelser - Helmer, Axel (Danish Yearbook of Musicology, 1977)
Review of: Sange af Peter Heise og P.E. Lange-Müller. Dansk Musik Antologi 004-010. Sang: Kirsten Buhl Møller, Edith Guillaume, Bodil Gøbel, Else Paaske, Ulrik Cold, Ole Hedegaard, Bent Norup, Kurt Westi. Akkomp.: Kaja Bundgaard, John Damgaard, Friedrich Gürtler, Kjell Olsson, Fjeld Simonsen, Támàs Vetö. EM! 6C 063-38102-08.